Pendampingan Pembuatan Surat Dan Penataan Administrasi Dalam Peningkatan Kualitas Administrasi Di Pondok Pesantren Al Muhajirin - Zenita Afifah Fitriyani; Ulfa Rahmawati; Fajar Budiyanto; Anna Kridaningsih; Harjo Lukito; Dian Indrianto; Ghozali Ghozali (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
The importance of making good letters and regular administrative arrangements need to be carried out to support good management administration, so the aim of this Community Service is to provide assistance in making letters using computer technology and administrative arrangements at the Al Muhajirin Islamic Boarding School. The method used in this community service consists of three stages, namely, the preparation stage, the implementation stage and the final stage. The results of this community service include sending material for making letters, material for administrative arrangements, practice of making letters and administration, as well as handing over printers and stationery. The hope from the results of this activity is that the writing of letters and administrative arrangements will be implemented immediately to produce good quality administrative management